Radiologic Evaluation of Small Renal Masses (II): Posttreatment Management - J. Santos; C. Deltoro; M. I. Martín; A. Marhuenda (Advances in Urology)
The increase in the detection of small renal masses (SRMs) and their best knowledge leads to a change in the therapeutic management of these lesions. The use of a less aggressive surgical technique or even an expectant attitude is the current tendency, in order to preserve as much renal function as possible. Imaging techniques are essential in the followup of these lesions. It allows us to know the postsurgical changes and possible complications due to treatment and the presence of local recurrence and metastases. Furthermore, a close radiological followup of SRM related to ablative treatments is mandatory. The purpose of this article is to reveal the imaging features of complications due to surgical or ablative treatments, local recurrence and metastasis, as well as their followup.